Nonlinear impact of the conventional monetary policy: A cross-country evidence - Jorge Pozo; Youel Rojas (Latin American Journal of Central Banking (LAJCB), 2025)
The possibility of non-linear responses to conventional monetary policy interventions has been a subject of ongoing research for a considerable period. However, the existing body of literature largely concentrates on analyzing individual economies or investigates only specific facets of these non-linearities. This paper aims to contribute to the literature and study the nonlinear impact of the conventional monetary policy, in two dimensions: direction and current monetary condition. This is the monetary policy effects depend on the monetary conditions and shock direction. Using a sample of both advanced and emerging economies, we find consistent evidence of asymmetric effectiveness of monetary policy. Initial movements of the policy rate are expected to have the largest effects, in contrast to the following movements in the same direction. Thus, the effectiveness of monetary policy wanes as the monetary stance tightens (i.e., as the policy interest rate rises). Conversely, the efficacy of expansionary monetary policy weakens as the monetary stance loosens (i.e., as the policy interest rate approaches its lower bound).
Keywords: E32; E52; G21; 330; Credit cycle; GPD cycle; Monetary policy; Non-linear effects